Kinematic adaptations during running: effects of footwear, surface, and duration - Hardin, E. C.; van den Bogert, A. J.; Hamill, J. (Medicine & Science in Sports & Exercise, 2004)
Repetitive impacts encountered during locomotion may be modified by footwear and/or surface. Changes in kinematics may occur either as a direct response to altered mechanical conditions or over time as active adaptations. PURPOSE: To investigate how midsole hardness, surface stiffness, and running duration influence running kinematics. METHODS: In the first of two experiments, 12 males ran at metabolic steady state under six conditions; combinations of midsole hardness (40 Shore A, 70 Shore A), and surface stiffness (100 kN x m, 200 kN x m, and 350 kN x m). In the second experiment, 10 males ran for 30 min on a 12% downhill grade. In both experiments, subjects ran at 3.4 m x s on a treadmill while 2-D hip, knee, and ankle kinematics were determined using high-speed videography (200 Hz). Oxygen cost and heart rate data were also collected. Kinematic adaptations to midsole, surface, and running time were studied. RESULTS: Stance time, stride cycle time, and maximal knee flexion were invariant across conditions in each experiment. Increased midsole hardness resulted in greater peak ankle dorsiflexion velocity (P = 0.0005). Increased surface stiffness resulted in decreased hip and knee flexion at contact, reduced maximal hip flexion, and increased peak angular velocities of the hip, knee, and ankle. Over time, hip flexion at contact decreased, plantarflexion at toe-off increased, and peak dorsiflexion and plantarflexion velocity increased. CONCLUSION: Lower-extremity kinematics adapted to increased midsole hardness, surface stiffness, and running duration. Changes in limb posture at impact were interpreted as active adaptations that compensate for passive mechanical effects. The adaptations appeared to have the goal of minimizing metabolic cost at the expense of increased exposure to impact shock.